PENGARUH WORD GROUPING ACTIVITIES DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR VOCABULARY SISWA PADA MATA PELAJARAN BAHASA INGGRIS DI SMP NEGERI 24 KERINCI - saputra, Bobi; Setiawan, Beni; Fernando, Riki (Jurnal Manajemen Pendidikan, 2017)
Results of learning and motivation of learners in learning English is not entirely satisfactory. One of the causes is developed and utilized learning methods provided by educators. This study aims to investigate the learning outcomes and learner motivation, that uses learning methods word grouping activities. This study is an experimental research conducted at Senior High School Negeri 24 Kerinci model 2x2 factorial design research. The study population were students of class VII with a sample consisting of two classes which serves as the control class and experimental class with the number of each learner is 20 people. In this study the data collected through questionnaires learning motivation and achievement test. Data analysis technique used is the t-test and anova. The results showed that: 1) Using t-test, study results showed that the Group of learners who are learning method using word grouping activities better compared to the results of a study group of learners who use conventional learning methods. 2) Using t-test, there is a significant difference between the results of the learning motivation of students of higher learning method using word grouping activities with participants who use conventional learning methods. 3) Using t-test, there is a significant difference between the results of the study, low motivation of learners use learning methods of word grouping activities with learners who use conventional learning methods. 4) There was no interaction between the methods of learning and learning motivation towards learning outcomes after a test of anova.